Effect of Co substitution and magnetic field on the morphologies and magnetic properties of CeO2 nanoparticles. Issue 9 (15th June 2019) - Yang, Zhigang; Zhao, Zhijia; Yu, Jianbo; Li, Jingyun; Ren, Zhongming; Ma, Shiqing; Ren, Shuxia; Yu, Gang
Abstract: Pure and Co-doped CeO2 nanoparticles were synthesized successfully by the solvothermal method. The effect of Co substitution and external magnetic field on the morphologies and magnetic properties of nanoparticles was investigated. Results showed that synthesized Co-doped CeO2 had the face-centered cubic structure and no other impurities existed in the samples with the increase of Co concentration from 5 to 75 wt%. The increasing Co concentration made the morphologies of Co-doped CeO2 nanoparticles vary from the hollow sphere, solid sphere to rod-like shape. The applied external magnetic field of 5T decreased the nanoparticle size effectively including the diameter of hollow sphere with low Co concentration and rod-like particles with high Co concentration. Moreover, the wall thickness of hollow sphere particles was also decreased from 35 nm to 18 nm for pure CeO2 . The Co-doped CeO2 nanoparticles showed the weak ferromagnetic behavior. With the increase of Co concentration, the saturation magnetization (Ms ) value increased first and then decreased. The Co-doped CeO2 with 30 wt% showed the highest value of 3.65 × 10 −2 emu/g (Ms ). The Ms value of Co-doped CeO2 prepared in 5T showed an increasing trend with the Co concentration. The highest value (Ms ) reached 4.21 × 10 −2 emu/g for doped CeO2 with 75 wt% Co.